PENGEMBANGAN MEDIA INFOGRAFIS DAN QUIZIZZ PADA MATA PELAJARAN FIQIH MATERI PERADILAN ISLAM DAN HIKMAHNYA KELAS XI DI MA DARUL ULUM - Iqbal Iqbal; Elsa Elsa; Dian Dian; Aziz Aziz (CV. ADIBA AISHA AMIRA, 2024)
This article highlights the important role of infographic and quizizz media development which aims to produce infographic and Quizizz media and the feasibility of using this media in learning Islamic justice material and its wisdom in class XI students at MA darul ulum. Islamic justice is an important aspect of understanding the Islamic legal system that is relevant in everyday life. In today's global era, the use of interactive media is needed to improve student understanding and make learning more interesting. The research method used is Research and Development (R&D) with the HANNAFIN and PECK models. The development process begins with the student needs assessment stage, followed by the infographic media design stage which emphasizes information about Islamic justice and its wisdom, and the function of justice functions. The third stage is the development and implementation of infographic media and quizizzes for class XI students at MA darul ulum. In addition, Quizizz is also used as an assessment tool that allows students to actively participate through interactive questions. Data collection techniques in this study were survey, observation, documentation and interviews. Judging from the survey in the form of questions on the quizizz media, the evaluation results show that the use of infographic media and Quizizz can significantly improve students' understanding of the material on Islamic justice and its wisdom.